Floristic patterns of the neotropical forests, savannas and scrublands with Trithrinax campestris (Arecaceae) in central Argentina - Zeballos, Sebastián Rodolfo (2021)
Trithrinax campestris is one of the palm species with the southernmost distribution in the Neotropics. Despite that the vegetation types in which T. campestris occurs are nowadays heavily threatened by land use and land cover changes, their floristic composition and structure are still to be documented. In order to characterize T. campestris habitats, the aim of this study was to describe the floristic composition of the vegetation types in which this palm occurs and their relationships with different environmental factors.Study area: The survey was conducted in central Argentina in an area comprising the southern extreme of the distribution of T. campestris in the following phytogeographic areas: Espinal, Lowland and Mountain Chaco.Methods: Following the Braun-Blanquet approach we collected 92 floristic relevés recording a total of 601 vascular plant species. Vegetation was classified through the ISOPAM hierarchical analysis. Bioclimatic and elevation data were related to the floristic data through the ISOMAP ordination. Remote-sensed images (Landsat TM, ETM+ and OLI) were used to characterize the fire frequency in the 92 stands.Results: Four vegetation types that differed in floristic composition and in diagnostic species were discriminated: 1.1 Celtis tala/Sida rhombifolia closed forest; 1.2 Aspidosperma quebracho-blanco/Prosopis kuntzei open forest; 2.1 Jarava pseudoichu/Vachellia caven open savanna; and 2.2 Acalypha variabilis/Nassella cordobensis scrubland. The ISOMAP ordination showed that differences in floristic composition were related to elevation, topography and climatic variables.Out of the 92 stands, only 21 showed the occurrence of fires during the period 1999?2018.Conclusions: Our results evidenced that vegetation types (forests, savannas and scrublands) comprising T. campestris developed in a wide range of environmental conditions. This is the first study that focuses on all vegetation types in which T. campestris occurs in central Argentina and it is relevant for conservation and sustainable management of the only native palm species in the flora of this part of the country.